Characterizing UNAM’s Open Education System Using the OOFAT Model - Cervantes-Perez, Francisco; Vadillo, Guadalupe; Bucio, Jackeline; Herrera, Alma (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2019)
Mexico’s national university (UNAM) is a public mega university with a 46-year history in open education. This article presents an analysis based on the open, online, flexible provision of technology-enhanced higher education (OOFAT) model, developed by Orr and his colleagues (2018). The aim of this analysis was to characterize UNAM’s open and distance education system in terms of openness, flexibility, and its business model, in three distinct time periods. According to this analysis, the system has evolved in all areas, and at present has a content-focused approach in terms of flexibility and openness, which differs from the OOFAT at the center approach that is desired. The study also characterized the UNAM system’s business model as a prospector-like approach, which highlights the possibilities for instilling innovation through the schools that comprise this system. The analysis allowed for mapping the current situation and thus sheds light on defining the steps necessary for creating an integrally open system.